2016
DOI: 10.1158/0008-5472.can-15-3178
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic Switch between SOX2 and SOX9 Regulates Cancer Cell Plasticity

Abstract: Cell differentiation within stem cell lineages can check proliferative potential, but nodal pathways that can limit tumor growth are obscure. Here, we report that lung cancer cell populations generate phenotypic and oncogenic plasticity via a switch between differentiation programs controlled by SOX2 and SOX9, thus altering proliferative and invasive capabilities. In lung cancer cells, SOX2 bound the EPCAM promoter to induce EpCAM-p21-cyclin A2 signaling, encouraging cell proliferation as well as barrier prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 47 publications
(56 reference statements)
2
54
0
Order By: Relevance
“…HCC827 cells were kindly provided by Dr. Jeff Wang (Development Center for Biotechnology, Taiwan) and further certified via short tandem repeat-PCR DNA profiling in 2013 (37). H1975 cells were obtained from Dr. Wayne Chang (National Health Research Institutes, Taiwan) and further authenticated via EGFR sequencing analysis in 2015 (38). HCC827GR cells were established in our laboratory, as described in Supplementary Materials and Methods, and tested positive for human origin carrying specific EGFR mutations by EGFR sequencing analysis (Supplementary Fig.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…HCC827 cells were kindly provided by Dr. Jeff Wang (Development Center for Biotechnology, Taiwan) and further certified via short tandem repeat-PCR DNA profiling in 2013 (37). H1975 cells were obtained from Dr. Wayne Chang (National Health Research Institutes, Taiwan) and further authenticated via EGFR sequencing analysis in 2015 (38). HCC827GR cells were established in our laboratory, as described in Supplementary Materials and Methods, and tested positive for human origin carrying specific EGFR mutations by EGFR sequencing analysis (Supplementary Fig.…”
Section: Cell Culturementioning
confidence: 99%
“…Approval for this study was granted by the Institutional Review Board protocol number CRC-04-11-05. The public gene expression profiling datasets used in this study were analyzed as described previously (38). The sources of these gene expression profiling datasets are listed in Supplementary Table S5.…”
Section: Tissue Samples and Public Domain Data Analysismentioning
confidence: 99%
“…These findings support the notion that CEA expression patterns in patients can be altered by TKI treatment, and patients with changes in expression patterns of CEA In and CEA Pd may exhibit different responses toward subsequent chemotherapies after the EGFR-TKI treatment. We have previously reported that tumor heterogeneity is in part regulated by epigenetic control to generate lung cancer cells with distinct dissemination and chemoresistant properties 35 . Whether heterogeneous CEA expression patterns and related oncogenic properties in lung cancer cells are under epigenetic control requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SOX2 was expressed in highly proliferative but minimally invasive lung cancer cells; in contrast, cells with highly invasiveness capacity exhibited increased SOX9 expression but reduced SOX2 expression. The switch between SOX2 and SOX9 expression is epigenetically controlled and is important for determining cancer cell plasticity and metastatic progression [78]. Ectopic expression of SOX9 enhanced growth, invasion, and angiogenesis, whereas silencing of endogenous SOX9 markedly impaired tumor growth in prostate cancer.…”
Section: Sox9 and Cancermentioning
confidence: 99%